(untitled) (Fiep Bulletin - online, 2020)
In our country, as we have a moving rhythm, I gave life to an aposentadoria or aposentadoria, where, além da idade, six rhythms of life and six circles of amizade mudam. Muitos deles tornam-se highly sedentários e não realizam nenhum type of physical activity that predisposes to or different. Objective: The objective of this research work is to determine the fatigue for or development of recreational physical activity between 55 and 77 years of the Social Security Institute of Benjamin Aceval. Methodology: Amostra é composta for 30 idosos of the program of full life, being or instrument of data collection of a dated questionnaire. Or release of this experimental study, with quantitative and descriptive approach. Results: Os idosos não manifestaram dor, além de dançar, also a bicycle rack and also satisfied with health. Eles was mainly mulheres between 55 and 70 years. No research time, all the participants will affirm that they are not feeling, a small group has been hospitalized for the last few years, with constant agitation and constant persistence, and sometimes not even during the day. Regarding the consequences of the development of physical activities, they will not be disappointed or will not prevent you from doing their daily physical activities. Those who disseram feel discomfort ou dor mention that the most shaved area is between the legs and feet, joelhos, quadris e braços. Quanto às considered physiological, as doenças mais comuns são: primeiro, hipertensão, asthma ou doenças related to o pulmão, followed by diabetes and prone to bruises. Conclusion: The Useful Life Program is highly effective, considering that you wish that frequentam or program and practice of recreational dances increase your ability to perform your daily activities in a more agile and independent way, from a psychological point of view, be judged, safe and compatible. With its health, at the same time, despite the family environment, it is economically dependent on the level of academic schooling, and the dissemination will be more important with the weight of the person, as well as the environment and with the health service.